Metode Mengajar Tafsir Al Qur’an (Sub Bahasan Dalam Mata Pelajaran Al Qur’an Hadits) Pada Siswa Madrasah Aliyah - Budianto, Agus; Azka Zen, Millati; Ja’far Nashir, Muhammad (Edusifa: Jurnal Pendidikan Islam, 2023)
Education is a fundamental need for every human being on this earth. This article discusses the methods of teaching Qur'anic commentary that are appropriate for Madrasah Aliyah students. Tafsir of the Qur'an is an important part of the Islamic education curriculum, and the selection of appropriate teaching methods can affect students' understanding of the sacred text of the Qur'an. In this article, the author describes various methods of teaching tafsir, such as tahlili, muqaran, ijmali, and maudhu'i, as well as considerations in choosing a suitable method for Madrasah Aliyah students. The study emphasizes the importance of understanding the students' level of understanding and learning objectives in choosing an appropriate teaching method. With the right approach, Qur'anic exegesis teaching methods can be an effective instrument in helping Madrasah Aliyah students understand and appreciate Qur'anic messages in that educational context.